Epithelioid myofibroblastoma of the female breast. Issue 7 (July 2015) - Dekate, Jyoti Parag; Chetty, Runjan; Walsh, Jennifer; Perez-Ordoñez, Bayardo
Abstract Epithelioid myofibroblastoma of the breast is an extremely rare morphologic variant of myofibroblastoma composed of epithelioid cells comprising more than 50% of the tumour cell population. The tumour may display varied growth patterns but the main clinical significance of recognition of this variant lies in the fact that it mimics invasive lobular carcinoma of the breast, which has obvious clinical implications and management implications. The distinct morphologic features of epithelioid myofibroblastoma: lack of mitoses, and absence of significant atypia, along with its unique immunohistochemical profile aids in establishing the correct diagnosis.